The surgical treatment of Tennis Elbow by small Incision with local anesthesia - Dr. S. Baha. Karimi,; Dr Sayed Ahmadshah , (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: When non-operative treatment of tennis elbow fails; a surgical procedure can be performed to improve the associated symptoms.Methods: This manner was performed on 38 consecutive patients which treated surgically for lateral or medial epicondylitis. The indication for surgery was uncontrolled pain after six months of conservative treatment, more than 3 local injections of steroid and severe functional loss in occupational activities. The treatment results were assessed in terms of the pain using the visual analogue scale (VAS), Roles & Maudsley score, and Nirschl & Pettrone grade.Results: in this study 38 patients of tennis elbow were involved, the preoperative VAS scores of pain were medium at rest 4.96, daily activity 5.96, and 7.6 at sports. After surgery, the VAS scores regulated significantly (p < 0.01): 0.3 at rest, 1.53 daily activities, and 2.04 at sports. The preoperative Roles & Maudsley score was acceptable in 5 cases, and poor in 33 cases, which was changed to excellent in 22 cases, good in 14 cases, acceptable in 3 cases after surgery. Conclusions: The surgical treatment of Tennis Elbow by small Incision with local anesthesia appears to be one of effective methods for intractable lateral or medial epicondylitis.